Adverse prognostic impact of the KIT D816V transcriptional activity in advanced systemic mastocytosis - Naumann, Nicole; Lübke, Johannes; Baumann, Sofie; Schwaab, Juliana; Hoffmann, Oliver; Kreil, Sebastian; Dangelo, Vito; Reiter, Lukas; Bugert, Peter; Kristensen, Thomas; Sotlar, Karl; Haselmann, Verena; et al. (International journal of molecular sciences, 2021)
In systemic mastocytosis (SM), qualitative and serial quantitative assessment of the KIT D816V mutation is of diagnostic and prognostic relevance. We investigated peripheral blood and bone marrow samples of 161 patients (indolent SM (ISM), n = 40; advanced SM, AdvSM, n = 121) at referral and during follow-up for the KIT D816V variant allele frequency (VAF) at the DNA-level and the KIT D816V expressed allele burden (EAB) at the RNA-level. A round robin test with four participating laboratories revealed an excellent correlation (r > 0.99, R2 > 0.98) between three different DNA-assays. VAF and EAB strongly correlated in ISM (r = 0.91, coefficient of determination, R2 = 0.84) but only to a lesser extent in AdvSM (r = 0.71; R2 = 0.5). However, as compared to an EAB/VAF ratio ≤2 (cohort A, 77/121 patients, 64%) receiver operating characteristic (ROC) analysis identified an EAB/VAF ratio of >2 (cohort B, 44/121 patients, 36%) as predictive for an advanced phenotype and a significantly inferior median survival (3.3 vs. 11.7 years; p = 0.005). In terms of overall survival, Cox-regression analysis was only significant for the EAB/VAF ratio >2 (p = 0.006) but not for VAF or EAB individually. This study demonstrates for the first time that the transcriptional activity of KIT D816V may play an important role in the pathophysiology of SM.